(untitled) (American Journal of Education and Technology, 2024)
This study aimed to develop an intervention framework that would serve as a guide on how teachers can adopt technology integration in the academic curriculum by looking into the level of effects and challenges during its implementation. The study utilized a quantitative method specifically the descriptive design to assess the effects of technology integration and to measure the significant difference when grouped according to the demographic profile of the respondents. A convenience sampling technique was used to select a sample size of 30 public secondary school teachers. Also, an adapted questions from the study of Sarker et al. (2019), Jakubek (2023), and Hero (2019) was utilized. The findings highlighted that all dimensions of technology integration in terms of teaching style, teaching performance, teaching preference, job satisfaction, teachers’ commitment, teachers’ acceptance, and student engagement have significant and positive effects. Moreover, the teachers faced different challenges specifically the limited resources, inadequate training, and concerns about digital equity. Therefore, the study came up with an intervention framework that can be noted to contain various activities such as teacher professional development programs, curriculum integration and resource allocation, support mechanisms, teacher reflection and feedback, digital equity and accessibility, and research and evaluation. Thus, the implementation of this framework is suggested for future research to ensure its effectiveness in the educational context.